Comparative Analysis of Agricultural Water Footprint Changes in Guangdong and Guangxi and Their Driving Forces - QIU Yaliu; ZHENG Jiuyu; ZENG Wen; CAO Xinchun (Renmin Zhujiang)
To identify the agricultural water footprints in Guangdong Province and Guangxi Zhuang Autonomous Region and their influencing factors,we quantified the agricultural water footprints in Guangdong and Guangxi over 1996—2018 and their composition and revealed the driving mechanism of agricultural water footprint intensity and its regional differences.The average annual agricultural water footprints in Guangdong and Guangxi were 29.88 Gm3 and 41.37 Gm3 respectively. Both of them increased with time to the extent that the agricultural water footprint of Guangxi in 2018 was about 1.5 times that of Guangdong. The combined water footprint ratio of cereals and fruits in Guangdong was as high as 80.4%.The agricultural water footprints of cereals,fruits,and sugar in Guangxi were about 12 Gm3 each and accounted for 89.5% of the total.On the whole,the agricultural water footprint intensity showed a trend of rising-falling-rising.The composition of the water footprint manifested the relationship of blue water footprint<grey water footprint<green water footprint,and the green water footprint was dominant. In addition to precipitation,economic development is the main driving factor of the agricultural water footprint intensity in Guangdong,while agricultural production factors in Guangxi cannot be ignored.The results can provide a reference for the formulation of regulation strategies for different agricultural water footprints.